2021
DOI: 10.1186/s12978-021-01126-7
|View full text |Cite
|
Sign up to set email alerts
|

'Does HPV affect my fertility?' Reproductive concerns of HPV-positive women: a qualitative study

Abstract: Background Reproductive health changes can occur following infection with Human papillomavirus. HPV is the most prevalent sexually transmitted infection causing a variety of clinical manifestations ranging from warts to cancer. This study aimed to explore the reproductive concerns of women infected with HPV. Methods In this qualitative study, we used the conventional content analysis approach, with the aid of MAXQDA.10 software, to analyze data ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…A review of literature shows that the studies conducted on HPV are mostly focused on women, and such matters as quality of life [ 10 ], marital adaptation to the infection (using a quantitative approach) [ 11 ], vaccination [ 12 ], the psycho-sexual effects of being diagnosed with HPV [ 13 , 14 ], women’s experiences of facing their infection [ 15 ], women’s psychological responses to positive HPV test [ 16 ], the information management processes of women living with HPV [ 17 ], and reproductive concerns of HPV- positive women [ 18 ]. Research findings show that testing positive for human papillomavirus is accompanied by feelings of shame, stigma, self-deprecation, regret, anxiety and concern [ 16 , 18 , 19 ]. To the best knowledge of the authors, no work of research has addressed the process of adaptation in men and women with HPV.…”
Section: Introductionmentioning
confidence: 99%
“…A review of literature shows that the studies conducted on HPV are mostly focused on women, and such matters as quality of life [ 10 ], marital adaptation to the infection (using a quantitative approach) [ 11 ], vaccination [ 12 ], the psycho-sexual effects of being diagnosed with HPV [ 13 , 14 ], women’s experiences of facing their infection [ 15 ], women’s psychological responses to positive HPV test [ 16 ], the information management processes of women living with HPV [ 17 ], and reproductive concerns of HPV- positive women [ 18 ]. Research findings show that testing positive for human papillomavirus is accompanied by feelings of shame, stigma, self-deprecation, regret, anxiety and concern [ 16 , 18 , 19 ]. To the best knowledge of the authors, no work of research has addressed the process of adaptation in men and women with HPV.…”
Section: Introductionmentioning
confidence: 99%
“…In a mixed-method study conducted in the United States, 30 of 94 women who planned on getting pregnant indicated that their HPV test results would change their future pregnancy plans. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Throughout pregnancy, HPV-related lesions such as condyloma acuminata tend to significantly increase in size and number, oftentimes requiring local treatment after the first trimester [127][128][129]. However, in some cases, large lesions may obstruct the urinary tract and/or the birth canal, thus prompting the recommendation of cesarean delivery [127,128,130].…”
Section: Hpv Infection During Pregnancymentioning
confidence: 99%